A comparison of BMI and Lipid Profile in patients with metabolic syndrome and Type 2 Diabetes Mellitus - Asha Augusthy; Suchanda Sahu; Ashok Kumar Jeppu; Seema Jawalekar; Vijaya Marakala; Anitha Maria Thomas Thattil (International Journal of Medical Research and Review, 2017)
Introduction: Diabetes mellitus is a metabolic disease known by chronic hyperglycemia which results from defective insulin action and secretion. Metabolic syndrome consists of a constellation of metabolic abnormalities that confer increased risk of diabetes mellitus. The aim of the present study was to study BMI and lipid profile in patients with metabolic syndrome and type 2 diabetes mellitus.Materials and methods: 50 controls, 50 individuals with metabolic syndrome and 50 individuals with type 2 diabetes mellitus were selected by purposive sampling technique. BMI was calculated and serum levels of cholesterol, triglycerides, LDL, VLDL and HDL were estimated in controls and cases.Results: BMI, serum triglycerides, VLDL, cholesterol/HDL ratio were significantly increased (p<0.05) and serum HDL levels were significantly decreased (p<0.05) in metabolic syndrome and type 2 diabetes compared to controls.Conclusion: Our study concluded that there is significant dyslipidemia in patients with metabolic syndrome and type 2 diabetes mellitus.